Pulmonary rheumatoid nodules leading to spontaneous pneumothorax - Dewan, KR; Nanda, SK; Twayana, RS (Journal of College of Medical Sciences-Nepal, 2012)
Several pulmonary diseases are associated with spontaneous pneumothorax, including bronchial asthma, chronic obstructive airway disease, bronchiectasis, pneumonia, abscess, primary or metastatic cancer, and chronic interstitial lung disease.1 Spontaneous pneumothorax secondary to rheumatoid nodules which is one of the extra-articular manifestations of rheumatoid arthritis is rare but occasionally described.2There are some reports resulting in spontaneous pneumothorax especially on patients on methotrexate or leflunomide treatment.3We describe a case of rheumatoid arthritis who was on methotrexate therapy from a long time complicating in right sided spontaneous pneumothorax. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 57-60 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6729